Standard Digital Video Analysis and Engineering Field Controls - Tom Treleaven (International Society of Explosives Engineers, 2000)
The success of any blast is dependent on the accuracy of the blast design and the field controls used on the shot. This point cannot be over emphasized because when the geometry is not measured and/or field controls are not properly implemented, it can often have devastating effects on the final blast results. Thus drilling accuracy, tiont row burden control, explosive confinement, energy distribution, explosive selection, timing and structural geology become critical parameters in the design of successful blasts. Understanding the actual dynamics of the blast and why certain results were achieved is the fast step in optimizing a blast design. As stated by R. Frank Chiappetta, “Of all the blast monitoring systems available today, high speed videography still remains as the best stand alone instrumentation system for blast diagnostics.” Over the past years I have analyzed hundreds of blasts using either high-speed lowcams (500 frames per second) cameras or standard digital (30 frames per second). These analyses confirm, without a doubt, that shot geometry, in combination with structural geology, is the most important factor in overall blast results. Drilling accuracy is the single most important component in efficient blasting. Having equal mass associated with an equivalent energy is the basis in which blasts are designed. When drilling inaccuracy or borehole deviation occurs, not only is the energy unevenly distributed, but the basis of all design calculations becomes invalid. Over the past several years, quarry and mining operations have employed the use of boretracking measuring devices to measure borehole deviation and hole toe locations. In cases of operations using top hammer drills, it was discovered that the amount of deviation was significant and far greater than they believed they had. Set up error, improper drilling techniques and bit wear were some of the contributing factors. Through video anaysis of boretracked blasts, blast results were directly linked to drilling ..accuracy. The comparisons here took into account blast design, energy factors and hole sequencing.